Applicability of Hydrologic Response Units in low topographic relief catchments and evaluation using high resolution aerial photograph analysis. (July 2016) - Khan, Urooj; Tuteja, Narendra Kumar; Sharma, Ashish; Lucas, Stuart; Murphy, Brian; Jenkins, Brian
Abstract: Topography and geomorphology of a catchment are major drivers of runoff generation. In an earlier publication by the authors, a novel approach of delineating Hydrologic Response Units (HRUs) was investigated with reference to high topographic relief catchments. In the present study, this approach is evaluated for low topographic relief catchment and found to be applicable. To verify the proposed HRUs delineation logic, the thresholds derived from the DEM analysis are evaluated here at catchment scale using high resolution aerial photograph analysis and associated site visits. The thresholds derived from the DEM analysis are found in the same range as obtained from the aerial photographs analysis. The adequacy of the HRUs delineation approach is further verified by soil moisture movement modelling across four cross-sections and sensitivity analysis test for one cross-section in the Little River catchment which further supports the application of HRUs delineation approach in low topographic relief catchment. Highlights: Evaluation of HRUs using high resolution aerial photographs. Extension of HRUs in low topographic relief catchment. Analysis of upslope areas of channel head in the different rock types. Verification of HRUs using soil moisture movement modelling.